2019
DOI: 10.14283/jfa.2019.10
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impact of Hospitalizations in Us Adults With Sarcopenia

Abstract: ackground: Sarcopenia is characterized by progressive loss of muscle mass with corresponding decline in strength and/or physical function. The economic burden of sarcopenia-associated disability is considerable in the US. Objective: To estimate the cost of hospitalizations in US adults with sarcopenia categorized by age, sex, and race/ethnicity. Design, setting and participants: A retrospective, prevalence based, economic burden study, consisting of 4011 adults aged ≥40 years with and without sarcopenia. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
85
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 25 publications
0
85
0
Order By: Relevance
“…conducted an epidemiological survey on people aged 68–82 in Canada, which showed that the prevalence of sarcopenia was 38.9% in men and 17.8% in women. According to a survey in the USA in 2019, the total hospitalization cost of patients with sarcopenia was approximately 40.4 billion US dollars, which represents a huge economic burden on the health care system of the USA 12 . In addition, data from the UK 13 and the Czech Republic 14 also show that muscle weakness (including sarcopenia) can lead to an increase in direct medical costs.…”
Section: Introductionmentioning
confidence: 99%
“…conducted an epidemiological survey on people aged 68–82 in Canada, which showed that the prevalence of sarcopenia was 38.9% in men and 17.8% in women. According to a survey in the USA in 2019, the total hospitalization cost of patients with sarcopenia was approximately 40.4 billion US dollars, which represents a huge economic burden on the health care system of the USA 12 . In addition, data from the UK 13 and the Czech Republic 14 also show that muscle weakness (including sarcopenia) can lead to an increase in direct medical costs.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis included data from 4011 subjects during the period from 1999 to 2004. The analysis showed that 15.1% of individuals had sarcopenia and those in that group had about twice the odds of hospitalization compared with individuals without sarcopenia [2]. Osteoporosis often develops "silently" with patients often not learning of their condition until a fracture occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our knowledge, the designed economic model in present study is the first full economic evaluation model to compare sarcopenia screening strategies, which due to all limitations of information, tried to be designed and implemented systematically and step by step based on the best available evidences. Previous studies have focused more on the clinical features of the sarcopenia and in some cases the economic costs of the disease, such as the study of Janssen et al (2004) and Goates et al (2019) in the US [33,52] and the study of Sousa et al (2016) in Portugal [53].…”
Section: Discussionmentioning
confidence: 99%